2022
DOI: 10.2196/30811
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Mobile Phone HIV Adherence Support for Men Who Have Sex With Men in the Philippines Connect for Life Study: Mixed Methods Approach to Intervention Development and Pilot Testing

Abstract: Background The HIV epidemic in the Philippines is one of the fastest growing epidemics globally, and infections among men who have sex with men are rising at an alarming rate. The World Health Organization recommends the use of mobile health (mHealth) technologies to engage patients in care and ensure high levels of adherence to antiretroviral therapy (ART). Existing mHealth interventions can be adapted and tailored to the context and population served. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Many mHealth interventions for medication adherence among PWH have been tested in recent years within the US [ 53 – 65 ] and abroad [ 66 77 ]. Past studies have identified usability, acceptability and feasibility of mHealth designed for PWH [ 53 , 55 , 60 , 61 , 67 , 69 , 73 , 74 ] and some have demonstrated efficacy in improving adherence to ART in the short-term [ 32 , 53 , 55 , 60 , 66 , 70 , 73 , 74 ]. Among mHealth interventions for PWH in the US, limited studies have recruited or plan to recruit Latino populations specifically [ 32 , 53 55 , 57 , 58 , 60 , 61 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many mHealth interventions for medication adherence among PWH have been tested in recent years within the US [ 53 – 65 ] and abroad [ 66 77 ]. Past studies have identified usability, acceptability and feasibility of mHealth designed for PWH [ 53 , 55 , 60 , 61 , 67 , 69 , 73 , 74 ] and some have demonstrated efficacy in improving adherence to ART in the short-term [ 32 , 53 , 55 , 60 , 66 , 70 , 73 , 74 ]. Among mHealth interventions for PWH in the US, limited studies have recruited or plan to recruit Latino populations specifically [ 32 , 53 55 , 57 , 58 , 60 , 61 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Behavior change techniques related specifically to ART adherence were informed by the information-motivation-behavioral skills model of ART adherence [ 53 ]. Each service in the intervention package was designed to address ≥1 of the 3 main components that drive behavior in the Capability Opportunity Motivation–Behavior model, as outlined in Figure 2 [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The FGDs were transcribed, transcripts were manually coded using a deductive coding methodology to group responses by topic areas in the FGD guide, subtopics were assigned through line-by-line coding, and data were consolidated in a structured template that enabled identification of salient themes. Results from the FGDs in the formative and pilot phases informed the content and structure of the intervention and helped to identify implementation issues early in the project [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mobile application provides participants one-on-one virtual communication with case managers, appointment reminders, services support information, and educational articles [ 43 ]. A similar interactive mHealth intervention being tested in the Philippines provides MSM with medication adherence reminders, adherence feedback, symptom reporting, and health tips [ 44 ]. The Adam's Love platform described above has been used to support more comprehensive case management where potential clients for PrEP were provided online counseling, appointment bookings, and quick response code e-tickets to present at check-in.…”
Section: Comprehensive Virtual Case Managementmentioning
confidence: 99%